Comparison of Efficiency and Security of AES, Blowfish, and ChaCha20 Cryptographic Algorithms on Image and Document Files - Bintang Timur, Muhammad Bagus; Royansyah, Royansyah; Kusumaningsih, Dewi (Innovation in Research of Informatics (Innovatics), 2025)
This study presents a comparative analysis of the Advanced Encryption Standard (AES), Blowfish, and ChaCha20 cryptographic algorithms in terms of their efficiency and security when applied to image and document files. The growing need for secure data transmission and storage has highlighted the importance of selecting suitable encryption algorithms based on specific file types and operational contexts. In this research, various sample files in image (JPG, PNG) and document (PDF, DOCX) formats were encrypted using the three algorithms. Performance was measured based on encryption and decryption time, CPU and memory usage, and file size changes after encryption. Security evaluation focused on resistance to brute-force attacks, key length strength, and algorithmic robustness. The experimental results indicate that ChaCha20 demonstrated superior performance in terms of processing speed and resource efficiency, especially on low-power systems. AES, while slightly slower, offered a high level of security and is widely trusted for sensitive document encryption. Blowfish, although fast, showed limitations in handling larger files and is less favored due to its shorter block size. This study concludes that no single algorithm is universally optimal; instead, the choice should depend on the specific use case, balancing efficiency and security requirements. These findings provide useful insights for practitioners and researchers in selecting appropriate cryptographic methods for protecting digital assets.